Phylogenetic studies and modern classification of the Pyraloidea (Lepidoptera) - SOLIS, M. ALMA (Revista Colombiana de Entomología, 2007)
Pyraloidea, the third largest superfamily of the Lepidoptera, is comprised of two families Pyralidae and Crambidae. The history of families previously placed in the Pyraloidea is discussed. The group now includes about 16,000 species worldwide. morphologically, the superfamily is defined by a basally scaled proboscis and the presence of abdominal tympanal organs. The larvae of many species are economically important pests of crops (e. g.: sugarcane, corn, rice), and stored products such as seeds and grains. Currently 22 subfamilies comprise the Pyraloidea; only the 19 subfamilies that occur in the Western Hemisphere are discussed. There is a paucity of recent research using cladistic methods and phylogenetic analyses across all taxa.